Hadith #42 - Sunan al-Nasa'i - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ahmed bin Suliaman أحمد بن سليمان; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; ibn Mas'ud; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan al-Nasa'i)
“The Prophet (ﷺ) wanted to defecate, and he told me to bring him three stones. I found two stones and looked for a third, but I could not find any, so I picked up a piece of dung and brought them to the Prophet (ﷺ). He took the two stones and three away the dung and said: “This is Riks.” Abu ‘Abdur-Rahman (An-Nasai’) said: Riks is the food of the jinn.
Grade:

Hadith #128 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Asim al-Ahwal عاصم الأحول; Malik bin Mghwl مالك بن مغول; Safwan bin 'Assal; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان; Zar bin Habaysh bin Habasha زر بن حبيش بن حباشة; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan al-Nasa'i)
“I asked Safwan bin ‘Assal about wiping over the Khuffs, and he said: ‘The Messenger of Allah (ﷺ) used to tell us, when we were travelling, to wipe over our Khuffs and not take them off for three nights in the event of defecating, urinating or sleeping; only in the case of Janabah.'”
Grade:

Hadith #245 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin Suliaman أحمد بن سليمان; Aisha bint Abi Bakr; al-Husain bin Dhakwan al-Mua'lam الحسين بن ذكوان المعلم المكتب; Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan al-Nasa'i)
“I asked ‘Aishah about how the Messenger of Allah (ﷺ) performed Ghusl from Janabah. She said: ‘The Messenger of Allah (ﷺ) used to pour water onto his hands three times, then he would wash his private part, then he would wash his hands, then rinse his mouth and nose, then pour water onto his head three times, then pour water over the rest of his body.'”
Grade:

Hadith #246 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin Suliaman أحمد بن سليمان; Aisha bint Abi Bakr; Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“A vessel would be brought to the prophet (ﷺ) then he would pour water on his hand three times and wash them, then he would pour water with his right hand onto his left and wash off whatever was on his thighs. Then he would wash his hands, rinse his mouth and nose, pour water on his head three times, then pour water over the rest of his body.”
Grade:

Hadith #451 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Zubair bin Ady al-Hmdany الزبير بن عدي الهمداني اليامي; ibn Mas'ud; Malik bin Mghwl مالك بن مغول; Talha bin Msrf bin 'Amr طلحة بن مصرف بن عمرو بن كعب; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said: ‘Allah, the Mighty and Sublime, enjoined fifty prayers upon my Ummah, and I came back with that until I passed by Musa, peace be upon him, who said: ‘What has your Lord enjoined upon your Ummah?’ I said: ‘He has enjoined fifty prayers on them.’ Musa said to me: ‘Go back to your Lord, the Mighty and Sublime, for your Ummah will not be able to do that.’ So I went back to my Lord, the Mighty and Sublime, and He reduced a portion of it. Then I came
Grade:

Hadith #528 - Sunan al-Nasa'i - Abdah bin 'Abdullah al-Saffar عبدة بن عبد الله الصفار; Ahmed bin Suliaman أحمد بن سليمان; Bdr bin 'Uthman al-Amwy بدر بن عثمان الأموي مولاهم; Sulaiman bin Da'ud bin al-Jarud سليمان بن داود أبو داود الطيالسي (Sunan al-Nasa'i)
“Jibril, peace be upon him, came to the Prophet (ﷺ) when the sun had passed its zenith and said: ‘Get up, O Muhammad, and pray Zuhr when the sun has passed its zenith.’ Then he waited until a man’s shadow was equal to his height. Then he came to him for ‘Asr and said: ‘Get up, O Muhammad, and pray ‘Asr.’ Then he waited until the sunset, then he came to him and said: ‘Get up, O Muhammad, and pray Maghrib.’ So he got up and prayed it when the sun had set. Then he waited until
Grade:

Hadith #529 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Husain bin Bashyr bin Salam الحسين بن بشير بن سلام; Kharjh bin 'Abdullah خارجة بن عبد الله بن سليمان; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan al-Nasa'i)
“Al-Hajjaj arrived, and we asked Jabir bin ‘Abdullah, who said: ‘The Messenger of Allah (ﷺ) prayed Zuhr at the time of intense heat, and ‘Asr when the sun was white and clear, and Maghrib when the sun set, and with ‘Isha’ it would depend – if he saw that the people had gathered, he would pray early, and if he saw that they had not come yet, he would delay it.'” Meaning, at the earliest time.
Grade:

Hadith #546 - Sunan al-Nasa'i - Abdullah bin Abi Labid عبد الله بن أبي لبيد; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin Suliaman أحمد بن سليمان; ibn Umar; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umar bin Sa'd bin 'Ubaid عمر بن سعد بن عبيد أبو داود (Sunan al-Nasa'i)
“Where is the one who was asking about the time for prayer? (It is) between these two times.”
Grade:

Hadith #680 - Sunan al-Nasa'i - Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Ahmed bin Suliaman أحمد بن سليمان; Hammad bin Salama حماد بن سلمة; Matruf bin Tarayf al-Harithi مطرف بن طريف; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري (Sunan al-Nasa'i)
“I heard the Messenger of Allah (S.A.W) say: ‘When you hear the Mu’adhdhin then say what he says, and do Salah upon me, for whoever does Salah upon me once, Allah will Salah upon him ten (times). Then ask Allah to grant me Al-Wasilah, which is a position in paradise which only one of the slaves of Allah will attain, and I hope that I will be the one. Whoever asks for Al-Wasilah for me, will be entitled to my intercession.'”
Grade:

Hadith #900 - Sunan al-Nasa'i - Abu Sa'id al-Khudri; Ahmed bin Suliaman أحمد بن سليمان; Ali bin Da'ud,Abu al-Mutawakkal al-Naji علي بن داود أبو المتوكل الناجي; Ja'far bin Sulaiman al-Daba'i جعفر بن سليمان الضبعي; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan al-Nasa'i)
When the Messenger of Allah (ﷺ) stood to offer a voluntary prayer he would say: ” Allahu Akbar Wajahtu wajhi lilladhi fataras-samawatiwal-arda hanifan musliman wa ma ana minal-mushrikin. Inna salati wa nusuki wa mahyaya wa mamati lillahi rabbil-alamin, la sharika lahu, wa bidhalika umirtu wa ana awwalul-muslimin. Allahumma antal-maliku la ilaha illa anta subhanaka wa bihamdik (Allah is Most Great. Verily, I have turned my face toward Him who created the Heavens and the Earth hanifa (worhsipp
Grade:

Hadith #1037 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Husain bin Dhakwan al-Mua'lam الحسين بن ذكوان المعلم المكتب; Ata' bin Abi Rabah عطاء بن أبي رباح; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan al-Nasa'i)
” ‘Umar said: ‘The Sunnah is to hold the knees.'”
Grade:

Hadith #1185 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Jabir bin Samra; Mas'ar bin Kadam مسعر بن كدام; Ubaidullah bin al-Qbtyh عبيد الله بن القبطية الكوفي; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) set out to bring about reconciliation among Banu ‘Amr bin ‘Awf. The time for prayer came, and the Mu’adhdhin went to Abu Bakr to tell him to gather the people and lead them in prayer. Then the Messenger of Allah (ﷺ) came and passed though the rows until he stood in the first row. The people started clapping to let Abu Bakr know that the Messenger of Allah (ﷺ) had come. Abu Bakr never used to turn around when he prayed, but when they clapped consistently
Grade:

Hadith #1278 - Sunan al-Nasa'i - Abdur Rahman bin Humaid bin 'AR عبد الرحمن بن حميد بن عبد الرحمن; Ahmed bin Suliaman أحمد بن سليمان; ibn Abbas; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Tawus bin Kaysan طاوس; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan al-Nasa'i)
The Messenger of Allah (ﷺ) said: “People should certainly stop lifting their gaze to the sky when they supplicate during the prayer, or they will lose their eyesight.”
Grade:

Hadith #1312 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Hudhayfah ibn al-Yaman; Malik bin Mghwl مالك بن مغول; Talha bin Msrf bin 'Amr طلحة بن مصرف بن عمرو بن كعب; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان; Zayd bin Wahb al-Jhny زيد بن وهب الجهني (Sunan al-Nasa'i)
“I heard Abu Hurairah say: ‘The Messenger of Allah (ﷺ) said: When one of you recites the tashahhud, let him seek refuge with Allah (SWT) from our things: From the torment of hell, from the torment of the grave, from the trials of life and death and from the evils of the Dajjal. Then let him pray for himself asking whatever he wants.'”
Grade:

Hadith #1326 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Farat bin Abi 'Abdur Rahman فرات بن أبي عبد الرحمن القزاز; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Jabir bin Samra; Ubaidullah bin al-Qbtyh عبيد الله بن القبطية الكوفي; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام (Sunan al-Nasa'i)
The Prophet (ﷺ) used to say salam to his right and to his left: As-salamu ‘alaykum wa rahmatullah, as-salamu alaykum wa rahmatullah (peace be upon you and the mercy of Allah, peace be upon you and the mercy of Allah) until the whiteness of his cheek could be seen from here, and the whiteness of his cheek from here.
Grade:

Hadith #1332 - Sunan al-Nasa'i - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Ahmed bin Suliaman أحمد بن سليمان; al-Bara' bin Azib bin al-Harith; Amr bin 'Awn/'Auf bin Aws; Hilal bin Abi Maymuna هلال بن علي بن أسامة; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said the salam then he performed two prostrations of forgetfulness while he was still sitting, then he said the salam.” He said: He mentioned it in the hadith of Dhul-Yadain.
Grade:

Hadith #1345 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Aisha bint Abi Bakr; Ya'la bin 'Ubaid bin Umayya al-Tanafasi يعلى بن عبيد بن أبي أمية الطنافسي (Sunan al-Nasa'i)
Mu’awiyah wrote to Al-Mughirah asking him to write him a hadith that he had heard from the Messenger of Allah (ﷺ). Al-Mughirah wrote to him (Saying): “I heard him say, when he finished the prayer: ‘La Ilaha Illallah wahdahu la sharika lah, lahul-mulk wa lahul-hamd wa huwa ‘ala kulli shay’in qadir (There is none worthy of worship except Allah (ﷺ) alone with no partner or associate. He is the Dominion and to Him be all praise, and He is able to do all things) three times.”
Grade:

Hadith #1358 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) used to observe I’tikaf during the middle ten days of the month, and after the twentieth (day of the month), he would come out on the twenty-first and go back to his home, and those who were observing I’tikaf with him would go back like him. Then he stayed one month on the night when he used to go back home, and he addressed the people and enjoined upon them whatever Allah (SWT) willed. Then he said: ‘I used to observe I’tikaf during these ten days, then I
Grade:

Hadith #1501 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Aswad bin Qays al-Bdy الأسود بن قيس العبدي; Samra bin Jundub; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tha'laba bin 'Aabad ثعلبة بن عباد; Umar bin Sa'd bin 'Ubaid عمر بن سعد بن عبيد أبو داود (Sunan al-Nasa'i)
“The sun eclipsed during the time of the Messenger of Allah (ﷺ). The Messenger of Allah (ﷺ) prayed and stood for a long time, then he bowed for a long time, then he stood up and (remained standing) for a long time.” (One of the narrators) Shu’bh said: “I think he said something similar concerning prostration.”- “He started weeping and blowing during his prostration and said: ‘Lord, You did not tell me that You would do that while I am asking You for forgiveness; You did not tel
Grade:

Hadith #1599 - Sunan al-Nasa'i - Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Ahmed bin Suliaman أحمد بن سليمان; Basr bin Sa'id al-Madni بسر بن سعيد المدني العابد; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Musa bin 'Uqba موسى بن عقبة; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي; Zayd ibn Thabit (Sunan al-Nasa'i)
“The black people came and played in front of the Prophet (ﷺ) on the day of ‘Eid. He called me and I watched them from over his shoulder, and I continued to watch them until I was the one who moved away.”
Grade:

Hadith #1606 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Nu'man bin Bashir ibn Sa'd; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan al-Nasa'i)
He met Ibn ‘Abbas and asked him about Witr. He said: “Shall I not lead you to one who knows best among the people of the world about the witr of the Messenger of Allah (ﷺ)?” He said: “Yes.” (Ibn Abbas) said: “It is ‘Aishah. So go to her and ask her (about witr) and then come back to me and tell me the answer that she gives you.” So I went to Hakim bin Aflah and asked him to go accompany me to her. He said: “I shall not go to her, for I told her not to say anything about these
Grade:

Hadith #1624 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Uthman bin 'Asim bin Husayn عثمان بن عاصم بن حصين أبو حصين (Sunan al-Nasa'i)
“When the Prophet (ﷺ) got up at night to pray Tahajjud, he said: Allahumma, lakal-hamdu anta nurus-samawati wal-ardi wa man fihinna wa lakal-hamdu anta qayyamus-samawati wal ardi wa man fihinna wa lakal-hamdu, anta haqqun wa wa’duka haqqun wal jannatu haqqun wan-nuru haqqun wan-nabiyyuna haqqun wa Muhammadan haqqun, laka aslant wa ‘alaika tawakkaltu wa bika amant. ( O Allah, to You be praise, You are the Light of the heavens and earth and whoever is in them. To You be praise, You are the
Grade:

Hadith #1703 - Sunan al-Nasa'i - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ahmed bin Suliaman أحمد بن سليمان; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; ibn Abbas; Sa'id bin Jubayr سعيد بن جبير الأسدي; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan al-Nasa'i)
Aishah told him: “The Messenger of Allah (ﷺ) would not say the taslim for two rak’ahs during witr.”
Grade:

Hadith #1705 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Husain bin Dhakwan al-Mua'lam الحسين بن ذكوان المعلم المكتب; Ali bin 'Abdullah bin 'Abbas علي بن عبد الله بن عباس بن عبد المطلب; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Husayn bin 'Abdur Rahman al-Salmi حصين بن عبد الرحمن السلمي; Muhammad bin 'Ali bin 'Abd. bin 'Abbas محمد بن علي بن عبد الله بن عباس; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan al-Nasa'i)
“In the first rak’ah of witr, the Messenger of Allah (ﷺ) used to recite: “GLorify the Name of your Lord, the Most High;” in the second; “Say: O you disbelievers!” and in the third; “Say: He is Allah, (the) One.”
Grade:

Hadith #1709 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Aisha bint Abi Bakr; al-Husain bin Dhakwan al-Mua'lam الحسين بن ذكوان المعلم المكتب; Amarh bin 'Umayr al-Tymy عمارة بن عمير التيمي; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Yahya bin al-Jazar al-Arni يحيى بن الجزار; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan al-Nasa'i)
The Prophet (ﷺ) got up at night and cleaned his teeth, then he prayed two rak’ahs, then he slept. Then he got up and cleaned his teeth, then he performed wudu and prayed two rak’ahs, until he had prayed six. Then he prayed witr with three rak’ahs, and prayed two rak’ahs.
Grade:

Hadith #1735 - Sunan al-Nasa'i - Abdul Malik bin Aby عبد الملك بن أبي سليمان; Abdur Rahman bin Abza; Ahmed bin Suliaman أحمد بن سليمان; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Sa'id bin 'Abdur Rahman bin Abza سعيد بن عبد الرحمن بن أبزي; Zubayd bin al-Harith زبيد بن الحارث اليامي (Sunan al-Nasa'i)
Ubayy bin Ka’b said: “The Messenger of Allah (ﷺ) used to recite in Witr: “Glorify the Name of your Lord, the Most High;” and “Say: O you disbelievers!;’ and ‘Say: He is Allah, (the) One.'”
Grade:

Hadith #1738 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Dhar bin 'Abdullah al-Marhabi ذر بن عبد الله المرهبي; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Sa'id bin 'Abdur Rahman bin Abza سعيد بن عبد الرحمن بن أبزي; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان; Zubayd bin al-Harith زبيد بن الحارث اليامي (Sunan al-Nasa'i)
“Shu’bah narrated to us, he said: Salamah and Zubaid informed me, from Dharr, from Ibn ‘Abdur-Rahman bn Abza from Abdur-Rahman, that the Messenger of Allah (ﷺ) used to recite in Witr: “Glorify the Name of your Lord, the Most High;” and “Say: O you disbelievers!;’ and ‘Say: He is Allah, (the) One.’ And when he said the taslim, he would say: Subhanal-Malikil-Quddus (Glory be to the Sovereign, the Most Holy) three times, raising his voice with Subhanal-Malikil-Quddus the third t
Grade:

Hadith #1803 - Sunan al-Nasa'i - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ahmed bin Suliaman أحمد بن سليمان; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; al-Musayb bin Rafa'i al-Asadi المسيب بن رافع الأسدي الكاهلي أبو العلاء; Umm Habibah bint Abi Sufyan; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan al-Nasa'i)
“I heard the Messenger of Allah (ﷺ) say: ‘Whoever prays twelve rak’ahs a day, Allah (SWT), the Mighty and Sublime, will build for him a house in Paradise.'”
Grade:

Hadith #1805 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Musayb bin Rafa'i al-Asadi المسيب بن رافع الأسدي الكاهلي أبو العلاء; Isma'il bin Abi Khalid al-Ahmsi إسماعيل بن أبي خالد الأحمسي; Umm Habibah bint Abi Sufyan; Unbasa bin Abi Sufyan; Ya'la bin 'Ubaid bin Umayya al-Tanafasi يعلى بن عبيد بن أبي أمية الطنافسي (Sunan al-Nasa'i)
“Whoever prays twelve rak’ahs in a day and prays before Zuhr, Allah (SWT) will build for him a house in Paradise.”
Grade:

Hadith #2026 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Jabir bin Samra; Malik bin Mghwl مالك بن مغول; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan al-Nasa'i)
“A man was buried with my father in the same grave and I felt restless until I brought him out and buried him on his own.”
Grade:

Hadith #2114 - Sunan al-Nasa'i - Abu Da'ud أبو داود السجستاني الأزدي; Ahmed bin Suliaman أحمد بن سليمان; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
‘I fasted Ramadan’ or ‘I prayed Qiyam throughout the whole month.”‘ I do not know whether he dislike self-praise or he said: “Inevitably there will be heedlessness and sleep.” (Da ‘if)
Grade:

Hadith #2137 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Ibn Sa'd محمد بن سعد البغدادي; Isma'il bin Abi Khalid al-Ahmsi إسماعيل بن أبي خالد الأحمسي; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي (Sunan al-Nasa'i)
“I was very keen to ask ‘Umar bin Al-Khattab about the two wives of the Messenger of Allah to whom Allah said: If you two turn in repentance to Allah, (it will be better for you), your hearts are indeed so inclined.” And he quoted the Hadith. He said concerning it:’ “The from his wives for twenty-nine days because of that, when Hafsah had made her disclosure to Aishah. He had said: ‘I will not enter upon them for a month,’ because he was so upset with them when Allah, the Mighty an
Grade:

Hadith #2148 - Sunan al-Nasa'i - Abdul Malik bin Aby عبد الملك بن أبي سليمان; Abu Hurairah; Ahmed bin Suliaman أحمد بن سليمان; Ata' bin Abi Rabah عطاء بن أبي رباح; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“The Messenger of Allah said: “The month is twenty-nine (days).”
Grade:

Hadith #2160 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Husain bin Dhakwan al-Mua'lam الحسين بن ذكوان المعلم المكتب; Ammara bin al-Q'aqa' bin Shabrma عمارة بن القعقاع بن شبرمة; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan al-Nasa'i)
“How long was there between them?” He said: “As long as it takes a man to recite fifty verses.”
Grade:

Hadith #2181 - Sunan al-Nasa'i - Abu Da'ud أبو داود السجستاني الأزدي; Ahmed bin Suliaman أحمد بن سليمان; Aisha bint Abi Bakr; Khalid bin Sa'd al-Kwfy خالد بن سعد الكوفي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
“The Messenger of Allah used to join Shaban to Ramadan.” ‘
Grade:

Hadith #2270 - Sunan al-Nasa'i - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ahmed bin Suliaman أحمد بن سليمان; Muhammad bin Harb al-Wasti محمد بن حرب بن حرمان النشائي; Musa bin Mrwan موسى بن مروان; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“When the Messenger of Allah was eating breakfast in Marr Az-Zahran, and Abu Bakr and ‘Umar were with him, he said: ‘(Come and eat) breakfast.” (Daif) He narrated it in Mursal form.
Grade:

Hadith #2282 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Ghaylan bin Jarir غيلان بن جرير المعولي; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Musa bin Abi Aa'isha موسى بن أبي عائشة; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan al-Nasa'i)
“I came to the Prophet to discuss something and he was eating breakfast. He said: ‘Come and eat.’ I said: ‘I am fasting.’ He said: ‘Come and I will tell you about fasting. Allah has waived half of prayer and fasting from the traveler, and he has granted a concession to pregnant women and the sick.”‘
Grade:

Hadith #2359 - Sunan al-Nasa'i - Abu Hurairah; Ahmed bin Suliaman أحمد بن سليمان; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Thabit bin Qays b. Shammas; Usamah ibn Zayd; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan al-Nasa'i)
“The Messenger of Allah did not fast any month more than Shaban; he used to fast (all of) it, or most of it.”
Grade:

Hadith #2363 - Sunan al-Nasa'i - Abu Da'ud أبو داود السجستاني الأزدي; Ahmed bin Suliaman أحمد بن سليمان; Aisha bint Abi Bakr; Khalid bin Sa'd al-Kwfy خالد بن سعد الكوفي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
“I said: ‘O Messenger of Allah, sometimes you fast, and you hardly ever break your hardly ever fast, except two days which, if you are fasting, you include them in your fast, and if you are not fasting, then you fast them on your own.’ He said: ‘Which two days?’ I said: ‘Monday and Thursday.’ He said: ‘Those are two days in which deeds are shown to the Lord of the worlds, and I like my deeds to be shown (to Him) when I am fasting.”‘
Grade:

Hadith #2451 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Ibrahim al-Nakha'i إبراهيم النخعي; Masrouq bin al-Ajda' مسروق بن الأجدع; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Ya'la bin 'Ubaid bin Umayya al-Tanafasi يعلى بن عبيد بن أبي أمية الطنافسي (Sunan al-Nasa'i)
“No Sadaqah is due on less than five Dhawd (head of camel), and no Sadaqah is due on less than five Awaq, and no Sadaqah is due on less than five Awsuq.”
Grade:

Hadith #2520 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; ibn Umar; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“Give Zakah of your fast.” The people started looking at one another. So he said: “Whoever is here of the people of Al-Madinah, get up and teach your brothers, for they do not know that the Messenger of Allah has enjoined Salaqatul Fitr upon young and old, free and slave, male and female; half a Sa’ of wheat or a Sa’ of dates or barely.” Al_Hasan said: ‘If Allah has given you more, then give more generously of wheat or something else.”‘
Grade:

Hadith #2548 - Sunan al-Nasa'i - Abdullah bin Tawus عبد الله بن طاوس; Abu Hurairah; Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Ahmed bin Suliaman أحمد بن سليمان; Tawus bin Kaysan طاوس; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي (Sunan al-Nasa'i)
“The Messenger of Allah said: “The best kind of charity is that which is given when you are rich, and the upper hand is better than the lower hand, and start with those for whom you are responsible.”‘
Grade:

Hadith #2559 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Qatada قتادة; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“While we were with the Messenger of Allah in the early hours of the morning, some people came who were naked and barefoot, with their swords hung (around their necks). Most of them, may all of them, belonged to the tribe of Mudar. The face of the Messenger of Allah changed when he saw them in poverty. He went in (to his house) then he came out and ordered Bilah to call the Adhan and then the Iqamah. He (the Prophet) prayed, tjem je addressed te,, (reciting the Verses): ‘O mankind! Be dutifu
Grade:

Hadith #2592 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Hkym bin Jbyr al-Asady حكيم بن جبير; ibn Mas'ud; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan al-Nasa'i)
“Shall I ask people (for help), O Messenger of Allah?” He said: “No, but if you have no alternative but to ask, then ask the righteous.”
Grade:

Hadith #2594 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Da'ud bin Shabwr داود بن شابور; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو; Sufyan bin 'Uyaynah سفيان بن عيينة; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan al-Nasa'i)
“By the One in Whose hand is my soul, if one of you were to take a rope and gather firewood on his back that would be better for him than coming to a man to whom Allah, the Mighty and Sublime, has given of His bounty and asking him (for help). Which he may or may not give.
Grade:

Hadith #2599 - Sunan al-Nasa'i - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Ahmed bin Suliaman أحمد بن سليمان; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي; Samra bin Jundub; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Zayd bin 'Uqba al-Fzary زيد بن عقبة الفزاري الكوفي (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Whoever asks when he has forty Dirhams I being too demanding when asking.”‘
Grade:

Hadith #2602 - Sunan al-Nasa'i - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Ahmed bin Suliaman أحمد بن سليمان; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hakim ibn Hizam; Mskyn bin Bkyr al-Hrany مسكين بن بكير الحراني أبو عبد الرحمن; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘It is not permissible to give charity to a rich man (or one who is independent of means) or to one who is strong and healthy.”‘
Grade:

Hadith #2643 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Fadl ibn al-'Abbas; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Yahya bin Abi Ishaq يحيى بن أبي إسحاق; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“A man from Khath’am came to the Messenger of Allah and said: ‘My father is an old man who cannot ride, and the command of Allah to perform Hajj has come. Will it be good enough if I perform Hajj on his behalf?’ He said: ‘Are you the oldest of his children?’ He said: ‘Yes.’ He said: ‘Don’t you think that if he owed a debt you would pay it off?, He’ said: ‘Yes.’ He said: ‘then perform Hajj on his behalf.”'(Daif)
Grade:

Hadith #2821 - Sunan al-Nasa'i - Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Ahmed bin Suliaman أحمد بن سليمان; Ata' bin Abi Rabah عطاء بن أبي رباح; Hammad bin Salama حماد بن سلمة; ibn Abbas; Qays ibn Sa'd ibn 'Ubadah (Sunan al-Nasa'i)
he was with Messenger of Allah. When they were partway to Makkah, he lagged behind with some companions of his whowere in Ihram, but he was not in Ihram. He saw an onager, so he mounted his horse, then he asked his companions to hand him his whip, but they refused. He asked them to hand him his spear, but they refused. He took it, then chased the onager and killed it. Some of the Companions of the Messenger of Allah ate from it but others refused. The caught up with the Messenger of Allah and as
Grade:

Hadith #2883 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Hafs bin Ghyath حفص بن غياث; ibn Mas'ud; Ibrahim al-Nakha'i إبراهيم النخعي; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan al-Nasa'i)
“The Messenger of Allah said: This Hosue will be attacked by an army, and they will be swallowed up by the earth in Al-Baida’.”
Grade:

Hadith #2908 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Mujahid bin Jabir مجاهد بن جبر; Syf bin Sulaiman سيف بن سليمان (Sunan al-Nasa'i)
“The Messenger of Allah said: “Were it not for the fact that my people’ – according to the narration of Muhammad he said: ‘Your people’ – ‘have recently left Jailiyyah, I would have knocked down the House and given it two doors.'” When Ibn Az-Zubair was in power, he gave it two doors.
Grade:

Hadith #3093 - Sunan al-Nasa'i - Abu Hurairah; Ahmed bin Suliaman أحمد بن سليمان; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Mu'ml bin al-Fadl مؤمل بن الفضل; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Shu'aib bin Abi Hamza شعيب بن أبي حمزة; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan al-Nasa'i)
: “The Messenger of Allah said: ‘I have been sent with concise speech and I have been supported with fear. While I was sleeping, the keys to the treasures of the Earth were brought to me and placed in my hands.’” Abu Hurairah said: “The Messenger of Allah has gone and you are acquiring them.”
Grade:

Hadith #3107 - Sunan al-Nasa'i - Abu Hurairah; Ahmed bin Suliaman أحمد بن سليمان; Isa bin Talha bin 'Ubaidullah عيسى بن طلحة بن عبيد الله; Ja'far bin Awn bin Ja'far جعفر بن عون بن جعفر; Mas'ar bin Kadam مسعر بن كدام; Muhammad bin 'Abdur Rahman محمد بن عبد الرحمن بن نوفل (Sunan al-Nasa'i)
“bring me a shoulder blade of a camel, or a tablet, and write: Not equal are those of the believers who sit (at home).” An-Nisa’ 4:95. An-Nisa’ 4:95.
Grade:

Hadith #3194 - Sunan al-Nasa'i - Abdullah bin Jabr عبد الله بن عبد الله بن جبر/ جابر; Abdullah bin Jbr عبد الله بن جبر بن عتيك الأنصاري; Ahmed bin Suliaman أحمد بن سليمان; Ja'far bin Awn bin Ja'far جعفر بن عون بن جعفر (Sunan al-Nasa'i)
“Campaigns are of two types. As for the one who seek the Face of Allah, obeys the imam, spends what is precious to him, is easy-going with his companion and avoids mischief, when he is asleep and when he is awake, it will all bring reward. But as for the one who fights to show off, and he disobeys the imam and does mischief in the land, he will not come back the same as when he left.” It was not simply be the case that he comes back with no good deeds to his credit, rather he will have a nu
Grade:

Hadith #3355 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Alqama bin Qays علقمة بن قيس بن عبد الله; ibn Mas'ud; Ibrahim al-Nakha'i إبراهيم النخعي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“Umar bin Al-Khattab said: ‘Do not go to extremes with regard to the dowries of women, for if that were a sign of honor and dignity in this world, or a sign of piety before Allah, the Mighty and Sublime, then Muhammad would have done that before you. But he did not give any of his wives, and none of his daughters were given, more than twelve Uqiyyah. A man may increase the dowry until he feels resentment against her and says: You cost me everything I own (‘Alaqul-Qirbah)'” “And I was a
Grade:

Hadith #3625 - Sunan al-Nasa'i - Abdullah bin 'Awn bin Artaban عبد الله بن عون بن أرطبان الخزار; Ahmed bin Suliaman أحمد بن سليمان; Aisha bint Abi Bakr; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Ibrahim al-Nakha'i إبراهيم النخعي; Muhammad bin al-Fadl 'Aram محمد بن الفضل السدوسي أبو النعمان عارم (Sunan al-Nasa'i)
(The same) was narrated from Ibn ‘Awn, from Nafi’, from Ibn ‘Umar.
Grade:

Hadith #3627 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Amir bin Sa'd ibn Abi Waqqas عامر بن سعد بن أبي وقاص; Amr bin Mnswr al-Nsa'iy عمرو بن منصور النسائي أبو سعيد; Sa'd bin Ibrahim سعد بن إبراهيم بن عبد الرحمن; Sa'd ibn Abi Waqqas; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
“It is not right for a Muslim who has anything concerning which a will should be made, to abide for more than three nights without having a written will with him.”
Grade:

Hadith #3629 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Mas'ar bin Kadam مسعر بن كدام; Sa'd bin Ibrahim سعد بن إبراهيم بن عبد الرحمن (Sunan al-Nasa'i)
“The Messenger of Allah did not leave behind a Dinar or a Dirham, or a sheep or a camel, and he did not leave any will.”
Grade:

Hadith #3645 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Mua'wiya bin Ishaq bin Talha معاوية بن إسحاق بن طلحة بن عبيد; Musa ibn Talha; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام (Sunan al-Nasa'i)
‘(O Messenger of Allah!) My father has died owing debts, and he has not left anything but what his date-palms produce. What his date-palms produce will not pay off his debts for years. Come with me, O Messenger of Allah, so that the creditors will not be harsh with me.’ The Messenger of Allah went to each heap, saying Salams and supplicating for it, then sitting on it. He called the creditors and paid them off, and what was left was as much as what they had taken.”
Grade:

Hadith #3683 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Amir al-Sha'bi عامر الشعبي; Isma'il bin Abi Khalid al-Ahmsi إسماعيل بن أبي خالد الأحمسي; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي (Sunan al-Nasa'i)
“I want to give this son of mine a slave as a present, and if you think that I should go ahead with it, I will go ahead.” The Messenger of Allah said: “Have you given a present to all your children?” He said: “No.” He said: “Then take (your present) back.”
Grade:

Hadith #3684 - Sunan al-Nasa'i - Abdullah bin 'Utba; Ahmed bin Suliaman أحمد بن سليمان; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Amir al-Sha'bi عامر الشعبي; Hiban bin Hilal حبان بن هلال; ibn Umar; Muhammad bin Hatim Al-Samayn محمد بن حاتم البغدادي - السمين; Zakaria bin Abi Za'idah زكريا بن أبي زائدة خالد (Sunan al-Nasa'i)
“Ask the Prophet to bear witness to what you have given to my son.” So he came to the Prophet and told him about that, and the Prophet did not want to bear witness to it.
Grade:

Hadith #3712 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; ibn Abbas; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tawus bin Kaysan طاوس; Ya'la bin 'Ubaid bin Umayya al-Tanafasi يعلى بن عبيد بن أبي أمية الطنافسي (Sunan al-Nasa'i)
“It is not permissible for anyone to give a gift then take it back, except a father.” Tawus said: “I used to hear the boys say: ‘O you who goes back to his vomit!’ But I did not realize that the Messenger of Allah had said this as a parable, until we heard that he used to say: ‘The likeness of the one who gives a gift then takes it back, is that of the dog which eats its vomit.'”
Grade:

Hadith #3713 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Hajjaj bin al-Minhal حجاج بن المنهال; ibn Abbas; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“Some of those who met the Prophet told us that he said: ‘The likeness of the one who gives (something), then takes back his gift, is that of a dog which eats, then vomits, then eats its vomit.'”
Grade:

Hadith #3728 - Sunan al-Nasa'i - Abdul al-Kareem bin Malik عبد الكريم بن مالك الجزري أبو سعيد; Ahmed bin Suliaman أحمد بن سليمان; Ata' bin Abi Rabah عطاء بن أبي رباح; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan al-Nasa'i)
“‘Umra (a gift given for life) belongs to the heir.”
Grade:

Hadith #3761 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; ibn Umar; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي; Musa bin 'Uqba موسى بن عقبة; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
“There is no lifelong gift. Whoever is given something as a lifelong gift, it belongs to him.”
Grade:

Hadith #3774 - Sunan al-Nasa'i - Abdur Rahman bin Samra; Ahmed bin Suliaman أحمد بن سليمان; al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“A man from Banu Ghifar told me, in the gathering of Salim bin ‘Abdullah, Salim bin ‘Abdullah said: ‘I heard ‘Abdullah -that is, Ibn ‘Umar- say: “The Messenger of Allah said: ‘Allah forbids you to swear by your forefathers.'”‘”
Grade:

Hadith #3783 - Sunan al-Nasa'i - Abdur Rahman bin Samra; Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Ahmed bin Suliaman أحمد بن سليمان; al-Hasan al-Basri الحسن البصري; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد (Sunan al-Nasa'i)
“Do not swear by your forefathers or by false gods (At-Tawaghit).”
Grade:

Hadith #3830 - Sunan al-Nasa'i - Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Ahmed bin Suliaman أحمد بن سليمان; Ayoub al-Sakhtiyani أيوب السختياني; ibn Umar; Nafie' نافع مولى ابن عمر; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي (Sunan al-Nasa'i)
“Umar had made a vow to spend a night in ‘Itikaf in Al-Masjid Al-Haram. He asked the Messenger of Allah about that, and he ordered him to perform the ‘Itikaf.”
Grade:

Hadith #3869 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Ibrahim bin Mhajr bin Jabir إبراهيم بن مهاجر بن جابر; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Mujahid bin Jabir مجاهد بن جبر; Rafi' bin Khadij bin Rafi'; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan al-Nasa'i)
“I will lease (something) from you until I reach Makkah for such and such a payment, and if I travel for a month or such and such -something that he named- I will give you such and such in addition.” They did not see anything wrong with that, but they did not like it if he said: “If I travel for more than a month I will deduct such and such from your lease.”
Grade:

Hadith #3891 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Sa'id bin Abi Sa'id; Tarq bin 'Abdur Rahman طارق بن عبد الرحمن البجلي الأحمسي الكوفي; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام (Sunan al-Nasa'i)
“The Prophet forbade Al-Haql and it is Al-Muzabanah.”
Grade:

Hadith #3975 - Sunan al-Nasa'i - Abu Hurairah; Ahmed bin Suliaman أحمد بن سليمان; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Mu'ml bin al-Fadl مؤمل بن الفضل; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Shu'aib bin Abi Hamza شعيب بن أبي حمزة; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan al-Nasa'i)
“I noticed that he was not there one night” and he quoted the rest of the Hadith.
Grade:

Hadith #3980 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Nu'man bin Salm al-Ta'ify النعمان بن سالم الطائفي; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan al-Nasa'i)
“When the Messenger of Allah , I will fight them for withholding it.’ ‘Umar, may Allah be pleased with him, said: ‘By Allah, as soon as I realized that Allah has expanded the chest of Abu Bakr for fighting, I knew that it was the truth.'”
Grade:

Hadith #3981 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Hasan bin Muhammad bin A'yn الحسن بن محمد بن أعين; al-Nu'man bin Salm al-Ta'ify النعمان بن سالم الطائفي; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan al-Nasa'i)
“The Messenger of Allah say such and such?’ He said: ‘By Allah, I do not separate Salah and Zakah, and I will fight whoever separates them.’ So we fought alongside him, and we realized that that was the right thing.”
Grade:

Hadith #3993 - Sunan al-Nasa'i - Abu Da'ud أبو داود السجستاني الأزدي; Ahmed bin Suliaman أحمد بن سليمان; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan al-Nasa'i)
‘Amr bin Aws told him that his father Aws said: “The Messenger of Allah said: ‘I have been commanded to fight the people until they bear witness to La ilaha illallah (there is none worthy of worship except Allah), then their blood and their wealth become forbidden to me, except for a right that is due.”
Grade:

Hadith #4027 - Sunan al-Nasa'i - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ahmed bin Suliaman أحمد بن سليمان; Anas ibn Malik; Ayoub al-Sakhtiyani أيوب السختياني; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
“Aishah said: ‘Do you not know that the Messenger of Allah said: It is not permissible to shed the blood of a Muslim, except a man who committed adultery after being married, or one who reverted to Kufr after becoming Muslim, or a life for a life.'”
Grade:

Hadith #4051 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Mughira bin Maqsam المغيرة بن مقسم; Amir al-Sha'bi عامر الشعبي; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Jarir bin 'Abdullah al-Bajli; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام (Sunan al-Nasa'i)
From the Messenger of Allah : “The Verse about Al-Muharabah was revealed concerning them.”
Grade:

Hadith #4089 - Sunan al-Nasa'i - Abdullah bin 'Amr bin al-'Aas; Ahmed bin Suliaman أحمد بن سليمان; Ibrahim bin Muhammad bin Talha إبراهيم بن محمد بن طلحة بن عبيد الله; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Whoever ties a know and blows on it, he has practiced magic; and whoever practices magic, he has committed Shirk; and whoever hangs up something (as an amulet) will be entrusted to it.'”
Grade:

Hadith #4117 - Sunan al-Nasa'i - Abu Bakra al-Thaqafi; Ahmed bin Suliaman أحمد بن سليمان; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Raba'i bin Harash bin Jahsh ربعي بن حراش; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ya'la bin 'Ubaid bin Umayya al-Tanafasi يعلى بن عبيد بن أبي أمية الطنافسي (Sunan al-Nasa'i)
“Defaming a Muslim is evildoing and fighting him is Kufr.” (Sahih Mawquf)
Grade:

Hadith #4212 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Da'ud bin Qays al-Fra'a داود بن قيس الفراء الدباغ; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan al-Nasa'i)
“Allah never sends a prophet or appoints a Khalifah but he has two groups of advisers: A group that tells him to do good and a group that tells him to do evil and urges him to do it. And the one who is truly protected is the one who is protected by Allah, the Mighty and Sublime.”
Grade:

Hadith #4215 - Sunan al-Nasa'i - Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Ahmed bin Suliaman أحمد بن سليمان; Ata' bin Abi Rabah عطاء بن أبي رباح; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Mujahid bin Jabir مجاهد بن جبر; Qays ibn Sa'd ibn 'Ubadah; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
the Messenger of Allah sent an army and appointed a man in charge of them. He lit a fire and said: “Enter it.” Some people wanted to enter it, and other said: “We are trying to keep away from it.” They mentioned that to the Messenger of Allah, and he said to those who had wanted to enter if: “If you had entered it you would have stayed there until the Day of Resurrection.” And he spoke good words to the others. And he said: “There is no obedience if it involves disobedience toward
Grade:

Hadith #4274 - Sunan al-Nasa'i - Adi ibn Hatim al-Tayyi'; Ahmed bin Suliaman أحمد بن سليمان; Amir al-Sha'bi عامر الشعبي; Asim al-Ahwal عاصم الأحول; Yazid bin Harun يزيد بن هارون; Zakaria bin Abi Za'idah زكريا بن أبي زائدة خالد (Sunan al-Nasa'i)
“I asked the Messenger of Allah about hunting with a Mi`rad. He said: ‘If you strike (the game) with its sharp point, then eat, but if you strike it with its broad side, then the animal has been killed with a blow.’ I asked him about dogs and he said: ‘If you release your dog and he catches (the game) but does not eat it, then eat, because his catching it is its slaughter. If you find another dog with your dog and you fear that it caught (the game) with him and k
Grade:

Hadith #4297 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Husain bin 'Ali bin al-Walid al-Ja'fi الحسين بن علي بن الوليد الجعفي; Rafi' bin Khadij bin Rafi'; Sa'id bin Masrooq Ath-Thawri سعيد بن مسروق الثوري; Ubaya bin Rafa' bin Rafi' عباية بن رفاعة بن رافع; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan al-Nasa'i)
“Whoever keeps a dog. Except a dog for hunting or herding livestock, two Qirats will be deducted from his reward each day.”
Grade:

Hadith #4719 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Bashayr bin al-Yasar al-Harithi al-Ansar بشير بن يسار مولى بني حارثة; Sa'id bin 'Ubaid al-Tai'i سعيد بن عبيد الطائي (Sunan al-Nasa'i)
“Qasamah existed during the Jahiliyyah, then the Messenger of Allah confirmed it in the case of an Ansari who was found slain in the dry well of the jews, and Ansar said: “The Jews kill our companion.”‘
Grade:

Hadith #4755 - Sunan al-Nasa'i - Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Ahmed bin Suliaman أحمد بن سليمان; Anas ibn Malik; Hammad bin Salama حماد بن سلمة; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan al-Nasa'i)
“Ali said: ‘The Messenger of Allah did not tell me anything that he did not tell the people, except what is in a sheet in the sheath of my word.’ They did not leave him alone until he brought out the sheet, and in it (were the words): ‘The lives of the believers are equal in value, and they hasten to support the asylum granted by the least of them, and they are one against others. But no believer may be killed in return for a disbeliever, nor one with a covenant while his covenant is in
Grade:

Hadith #4775 - Sunan al-Nasa'i - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Ahmed bin Suliaman أحمد بن سليمان; ibn Abbas; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Sa'id bin Jubayr سعيد بن جبير الأسدي; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan al-Nasa'i)
“We went out with the Messenger of Allah on the campaign of Tabuk, and there was a friend of ours with us, who fought with a man from among the Muslims. The man bit him on the forearm, so he pulled it away from his mouth and a tooth fell out. The man came to the Prophet, seeking blood money, but his brother and bite him like a stallion bites, then come and demand blood money? There is no blood money for that.” And the Messenger of Allah juddgedit to be invalid.
Grade:

Hadith #4801 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Muhammad bin Rashid al-Mkhwly محمد بن راشد المكحولي الخزاعي الدمشقي; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو; Sulaiman bin Musa al-Ashdaq سليمان بن موسى الأموي الأشدق; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“The accidental killing, which seems intentional, with a whip or stick, (the Diyah) is one hundred camels, of which forty should be (she-camels) which their young in their wombs.”
Grade:

Hadith #4815 - Sunan al-Nasa'i - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Abdullah bin Mughfal al-Mazni; Ahmed bin Suliaman أحمد بن سليمان; Kahmas bin al-Hasan al-Tamimi كهمس بن الحسن التميمي; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘The blood money of a woman (in the event of injury) is like the blood money of a man, up to one-third of the Diyah (for her life).”
Grade:

Hadith #4834 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Aswad bin Hilal al-Maharbi الأسود بن هلال المحاربي; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tha'laba bin Zahdam al-Hanzali (Sunan al-Nasa'i)
“A woman of Banu Lihyan struck her co-wife with a tent pole and killed her, and the slain woman was pregnant. The Messenger of Allah ruled that the Diyah was to be paid by the’Asbah of the killer, and that a slave should be given (as Diyah) for the child in her womb”.
Grade:

Hadith #5005 - Sunan al-Nasa'i - Abdullah bin Dinar عبد الله بن دينار العدوي; Abu Da'ud أبو داود السجستاني الأزدي; Abu Hurairah; Ahmed bin Suliaman أحمد بن سليمان; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Sufyan bin 'Uyaynah سفيان بن عيينة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
“I heard the Messenger of Allah say: “The Muslim is the one from whose tongue and hand the Muslims are safe, and the Muhajir is the one who forsakes (Hajara) that which Allah has forbidden to him.”
Grade:

Hadith #5051 - Sunan al-Nasa'i - Abu Da'ud أبو داود السجستاني الأزدي; Ahmed bin Suliaman أحمد بن سليمان; ibn Umar; Nafie' نافع مولى ابن عمر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan al-Nasa'i)
“Ten things are from the Sunnah: Using the Siwak, trimming the mustache, rinsing the mouth, rinsing the nose, letting the beard grow, trimming the nails, plucking the armpit hairs, circumcision, shaving the pubes and washing one’s backside.”
Grade:

Hadith #5117 - Sunan al-Nasa'i - Abu Hurairah; Ahmed bin Suliaman أحمد بن سليمان; al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umar bin Sa'd bin 'Ubaid عمر بن سعد بن عبيد أبو داود (Sunan al-Nasa'i)
“I heard the Messenger of Allah cursing Al-Mutanammisat, women who have their teeth separated, and women who have tattoos done, those who change the creation of Allah, the Mighty and Sublime.”
Grade:

Hadith #5184 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Ali ibn Abi Talib; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Ubaida bin 'Amr al-Salamani عبيدة بن عمرو; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“I heard ‘Ali say: ‘The Messenger of Allah forbade me- but I do not say that he forbade you- from wearing gold rings, Al-Qassi, and garments dyed with safflower, and reciting Qur’an while bowing.'”
Grade:

Hadith #5189 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Bara' bin Azib bin al-Harith; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan al-Nasa'i)
“The Messenger of Allah forbade me (from wearing) garments dyed with safflower, and from gold rings, and from wearing Al-Qassi, and that I recite Qur’an while I am bowing.”
Grade:

Hadith #5195 - Sunan al-Nasa'i - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Ahmed bin Suliaman أحمد بن سليمان; Burayda bin al-Husayb; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan al-Nasa'i)
“The Messenger of Allah forbade me to wear gold rings.”
Grade:

Hadith #5200 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Musa bin Da'ud al-Dby موسى بن داود الضبي أبو عبد الله; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan al-Nasa'i)
A man, among those who met the Prophet , wore a gold ring. A similar report.
Grade:

Hadith #5224 - Sunan al-Nasa'i - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ahmed bin Suliaman أحمد بن سليمان; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan al-Nasa'i)
The Messenger of Allah discarded it and said: “I will never wear it again.”
Grade:

Hadith #5313 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Amir al-Sha'bi عامر الشعبي; Ibrahim al-Nakha'i إبراهيم النخعي; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Mas'ar bin Kadam مسعر بن كدام; Mkhld bin Yazid al-Quraishi مخلد بن يزيد القرشي الحراني; Suwayd bin Ghaflah bin Awsajah سويد بن غفلة بن عوسجة; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Umar ibn al-Khattab; Uthman bin 'Asim bin Husayn عثمان بن عاصم بن حصين أبو حصين (Sunan al-Nasa'i)
“Muhammad said: ‘Whoever wears silk in this world, will not wear it in the Hereafter.'”
Grade:

Hadith #5394 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Fadl ibn al-'Abbas; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Yahya bin Abi Ishaq يحيى بن أبي إسحاق; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
The Prophet said: “You will be keen for governorship but it will be regret and loss on the Day of Resurrection. What a good position it is when they are alive, but how miserable their state when they die (and leave it behind).”
Grade:

Hadith #5458 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Ahmed bin Suliaman أحمد بن سليمان; Asim al-Ahwal عاصم الأحول; Mhadr Bdad Ma'jmh محاضر بضاد معجمة; Zayd bin Arqam (Sunan al-Nasa'i)
“The Messenger of Allah had supplications that he never omitted to recite. He used to say: ‘Allahumma inni a’udhu bika minal-hammi, wal-hazani, wal-‘ajzi, wal-kasali, wal-bukhli, wal-jubni, wa ghalabatar-rijal (O Allah, I seek refuge with You from worry, grief, incapacity, laziness, miserliness, cowardice and being overpowered by (other) men.)”
Grade:

Hadith #5483 - Sunan al-Nasa'i - Abu Da'ud أبو داود السجستاني الأزدي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ahmed bin Suliaman أحمد بن سليمان; Amr bin Maymun al-Aw'di عمرو بن ميمون الأودي أبو عبد الله; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
The Prophet said: “A’udhu billahi minal-kufri wad-dain. (I seek refuge with Allah from Kufr and debt.)” A man said: “Are you equating debt with Kufr?” He said: “Yes.”
Grade:

Hadith #5507 - Sunan al-Nasa'i - Abdur Rahman bin 'Abdullah bin Dinar عبد الرحمن بن عبد الله بن دينار; Abu Dharr al-Ghaffari; Ahmed bin Suliaman أحمد بن سليمان; Ja'far bin Awn bin Ja'far جعفر بن عون بن جعفر (Sunan al-Nasa'i)
When the Messenger of Allah traveled, he would say: “Allahumma inni a’udhu bika min wa’tha’is-safari, wa kabatil-munqalabi, wal-hawri ba’dal-kawri, wa da’watil-mazlumi, wa suw’il-munzari fil-ahli wal-mal (O Allah, I seek refuge with You from the hardships of travel and the sorrows of return, from loss after plenty, from the supplication of the one who has been wronged, and seeing some calamity befall my family or wealth.)”
Grade:

Hadith #5558 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; ibn Abbas; Ikrama عكرمة; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“The Messenger of Allah forbade Ad-Dubba’, Al-Muzaffat,” – and on one occasion he added: “An-Naqir,” – “and (he forbade) mixing At-Tamr (dried dates) with raisins, and Az-Zahuw with At-Tamr.”
Grade:

Hadith #5580 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Amir al-Sha'bi عامر الشعبي; ibn Umar; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Uthman bin 'Asim bin Husayn عثمان بن عاصم بن حصين أبو حصين (Sunan al-Nasa'i)
“The Messenger of Allah forbade mixing Al-Busr and raisins, and Al-Busr and dried dates, and he said: ‘Soak each one of them on its own.'”
Grade:

Hadith #5643 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; ibn Umar; Mnswr bin Hyan منصور بن حيان; Sa'id bin Jubayr سعيد بن جبير الأسدي; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
The Messenger of Allah forbade drinking from green pitchers, gourds and vessels carved from wood.
Grade: